Penyuluhan Cara Menjaga Kesehatan Mental Di Dunia Kerja Melalui Teknik Role Play Di Universitas Al-Khairiyah Cilegon - Dita Juwita Zuraida; Nurul Fajri; Afra Hasna (CV. Multi Kreasi Media, 2023)
Mental health problems in working-age adults are increasing. Knowledge about maintaining mental health in the workplace is still minimal for students, especially eighth semester students of Al-Khairiyah University Cilegon. This shows that there is a need to strengthen students on how to maintain mental health in the world of work. One way to strengthen students about how to maintain mental health is with lecture techniques accompanied by role play. The counseling was attended by 48 eighth semester students of Al-Khairiyah University. After the counseling was conducted, the results showed that 60.2% of participants felt more prepared to face the world of work.